2015
DOI: 10.1371/journal.pone.0126963
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Spatial Memory Disorder and Hippocampal Damage by Exposure to Electromagnetic Fields in an Alzheimer’s Disease Rat Model

Abstract: Although some epidemiological investigations showed a potential association between long-term exposure of extremely low frequency electromagnetic fields (ELF-EMF) and Alzheimer’s disease (AD), no reasonable mechanism can explain this association, and the related animal experiments are rare. In this study, ELF-EMF exposure (50Hz 400µT 60d) combined with D-galactose intraperitoneal (50mg/kg, q.d., 42d) and Aβ25–35 hippocampal (5μl/unilateral, bilateral, single-dose) injection was implemented to establish a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
0
25
1
Order By: Relevance
“…In order to explore the principle of compatibility in TCM, the treatment of AD with KXS was applied as the working model. Aβ 25-35 -and D-gal-induced rats and Aβ 25-35 -induced PC12 cells were applied to establish AD models [23,24]. Hence, we explained the therapeutic effects of KXS at the molecular, cellular, and animal levels and expounded the biological mechanism and synergism in fighting AD multidimensionally, which could provide research strategies in studying traditional formula.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the principle of compatibility in TCM, the treatment of AD with KXS was applied as the working model. Aβ 25-35 -and D-gal-induced rats and Aβ 25-35 -induced PC12 cells were applied to establish AD models [23,24]. Hence, we explained the therapeutic effects of KXS at the molecular, cellular, and animal levels and expounded the biological mechanism and synergism in fighting AD multidimensionally, which could provide research strategies in studying traditional formula.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that CREB is highly sensitive to ELF magnetic field exposure and the following changes have been observed: (1) Peak positions' shifts and intensity changes were highly noticeable for the bands of amide IV, amide VI and amide II (2). The loss of intensity implies that CREB exposure to magnetic field introduces a damping factor on the amplitude of oscillation which alters molecular vibrations at the bonding sites (3). No major changes in the amide III and amide I region have been observed (4).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that exposure to an extremely low-frequency electromagnetic field increases hippocampal neurogenesis and improves memory [1]. Rats exposed to ELF-MF during cognitive training performed better in both spatial learning and long-term retention of spatial memory [2][3][4]. Other studies have also shown that exposure to ELF-MF can increase the levels of amino acid neurotransmitters and increase the level of dopamine in the thalamus of rat brains [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 900 MHz GSM fields caused only modest increases in constitutive HSP70 and HSP90 expression and concomitantly decreased α‐synuclein expression, all of which were attributable to a 0.5 °C increase in temperature [Terro et al, ]. Recent reports using long‐term ELF EMF exposures suggest these did not aggravate disease in mouse models of Alzheimer's or amyotrophic lateral sclerosis [Liebl et al, ], and improved both spatial memory disorder and hippocampal damage in a rat model of Alzheimer's [Liu et al, ]. Further studies of EMF effects in tractable models of human neurodegenerative diseases are urgently needed, and any robust effects reported will require exact replication by several independent laboratories.…”
Section: Discussionmentioning
confidence: 99%